L’attitude, puis les arguments - Pirogowska, Ewa (Studia Romanica Posnaniensia, 2017)
The paper investigates the challenges posed by argumentation relying on a logical fallacy. The data has been obtained from a genuine interaction found in cyberspace. The aim of the study is to demonstrate that once a line of reasoning is arbitrarily imposed, a conversational schema emerges, even in spite of the fact that the messages are not consistently interlinked.